Evaluasi Kinerja Guru Sekolah Dasar di Kutai Timur - Syamsudin, Moh. (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
Teacher performance on learning process as one of the important in supporting the creation of effective education process especially in build discipline attitude and student learning result quality. However, when teacher failed to minimize student inappropriate behavior, it often make teacher lost its spirit and lazy to teach. Teacher performance has certain criterion. Their performance can be seen and measured based on competence specification or criterion that must be possessed by every teacher. In last few years many teachers that have certified, whereas their performance should be improve than before. Specifically, the purpose of research that was done : to find out the principal’s asessment to teachers performance elementary school level on kaubun sub dictrict Kutai Timur district. Method in this study apply statistic descriptive that conducted to describe certain phenomenon. Data collection performed to obtain information that related with phenomenon, condition, or certain variable and not intended to conduct hypothesist testing. This research conducted on elementary school of whole Kaubun District, East Borneo Province,. Variable in this research is principal’s asessment to teachers performance elementary school level on Kaubun sub dictrict Kutai Timur district.Based on the results of research on Teacher performance on learning process in Elementary School in on Kaubun sub dictrict Kutai Timur district be concluded that: 1) There are two (2) important component of the core activities, namely Planning evaluation of teacher performance and implementation of teacher performance evaluation 2) The performance evaluation conducted once a year by each school principal at the end of the school year between the months of May-June. Evaluations conducted simultaneously at all levels of both teachers and employees. Evaluating teacher performance in Kec. Kaubun means as an efforts to make professional teachers through performance evaluation.